XÁC ĐỊNH THÀNH PHẦN LOÀI, SỰ HIỆN DIỆN CỦA CÁC TÁC NHÂN GÂY BỆNH Rickettsia SFG VÀ Orientia tsutsugamushi TRÊN CHUỘT TẠI BA TỈNH TRÊN ĐỊA BÀN QUÂN KHU 2 - Trịnh, Văn Toàn; Võ, Viết Cường; Lê, Thị Lan Anh; Nguyễn, Văn Châu; Phan, Thị Lan Anh (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
SPECIES COMPOSITION, PRESENCE OF Rickettsia SFG AND Orientia tsutsugamushi PATHOGENS IN RAT AT THREE PROVINCES IN MILITARY REGION 2Spotted fever group Rickettsiae (SFG) and Scrub typhus infections, caused by obligate intracellular bacteria within two genera Orientia and Rickettsia SFG, the main host of which is the rodent. The study performed analysis of species composition of 103 rat samples collected at three provinces in Military Region 2 including: Dien Bien (35 samples), Son La (22 samples), and Phu Tho (46 samples), they have been collected from March to April, 2021, and detected the Rickettsia SFG and Orientia tsutsugamushi DNA by real-time PCR and nested-PCR. The results recorded that rat species belonged to Rattus flavipectus (42.7%), Rattus norvegicus (51.5%) were the most abundant, followed by Rattus germaini (3.9%) and Rattus nitidus (1.9%). The density of mice in Dien Bien was 6.7, Son La was 3.3, and Phu Tho was 8.5. The 6/35 (17.1%) positive samples for Rickettsia SFG were detected in Dien Bien by real-time PCR, in which 16,7% (5/30) was Rattus flavipectus and 50% (1/2) was Rattus norvegicus. In Son La, 7/22 samples were found as positive for Rickettsia SFG, accounting for 31.8%, of which 33.3% (3/9) was Rattus flavipectus, 30% (3/10) was Rattus norvegicus and 50% (1/2) was Rattus nitidus. In Phu Tho, 7/46 rats were found positive for Ricketsia SFG, accounting for 15.2% in which, Rattus norvergicus was 17.1% (7/41). However, among 103 rat samples, O. tsutsugamushi DNA was not detected by nested-PCR method. Currently, our results indicated the prevalence of Rickettsia SFG in Dien Bien, Son La and Phu Tho provinces.